2013
DOI: 10.1002/2013ja019200
|View full text |Cite
|
Sign up to set email alerts
|

Saturn's magnetospheric planetary period oscillations, neutral atmosphere circulation, and thunderstorm activity: Implications, or otherwise, for physical links

Abstract: Suggestions that the planetary period oscillations (PPOs) observed in Saturn's magnetosphere may be driven or influenced by neutral atmospheric perturbations motivate an exploratory comparison of PPO rotation periods with available tropospheric and stratospheric determinations. Nonpolar atmospheric rotation periods occupy the range ~10.2–10.7 h associated with the latitudinal jet structure, are similar north and south, and are independent of season, while PPO periods lie in a narrower partly overlapping range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 105 publications
0
19
0
Order By: Relevance
“…The abrupt changes noted by Fischer et al (2014) that occur after the beginning and near the end of the GWS event represent the first two of these transitions (defining interval E2), six of which have now been reported up until the end of 2013 as shown in Fig. 1 Cowley and Provan, 2013). Noting these differences in reported PPO properties, we make the statement of principle that the SKR and magnetic field phenomena cannot fundamentally show contrary properties, since both are believed to be directly related to the same underlying phenomenon, i.e.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The abrupt changes noted by Fischer et al (2014) that occur after the beginning and near the end of the GWS event represent the first two of these transitions (defining interval E2), six of which have now been reported up until the end of 2013 as shown in Fig. 1 Cowley and Provan, 2013). Noting these differences in reported PPO properties, we make the statement of principle that the SKR and magnetic field phenomena cannot fundamentally show contrary properties, since both are believed to be directly related to the same underlying phenomenon, i.e.…”
Section: Discussionmentioning
confidence: 93%
“…The magnetic data do suggest an increase in southern period in this interval, but by a factor of less than half that suggested by Fischer et al (2014) on the basis of their misidentification of the nature of the changes involved. The topic of the possible connection of these abrupt PPO changes with the GWS storm has previously been addressed by Cowley and Provan (2013), and need not be repeated here. We note, however, that while such changes certainly began during the GWS storm, many similar events have continued afterwards with ∼ 100-200-day cadence, as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, Hurley et al (2012) found no changes in temperature and chemical composition in the stratosphere related to the 2000 km sized thunderstorms located at 35 • south. Therefore, no relation was found by Cowley and Provan (2013) between those phenomena and the planetary period oscillations in Saturn's magnetosphere. Regarding the GWS, their main argument against a relation is that the start and end of the GWS are not exactly contemporaneous with the jumps in period in the magnetic field data, i.e., they assume that there should be a prompt response of the upper atmosphere to processes in the troposphere.…”
Section: On the Difficulty Of Proving The Skr-gws Relationmentioning
confidence: 97%
“…Dual periods were observed during Saturn's southern summer and near the equinox, but not during the northern spring. Apparently, neither the solar cycle nor the seasonal cycle offers a consistent pattern to the changing periodicities, a conclusion corroborated by recent reviews of non‐ENA periodicities [ Kimura et al ., ; Cowley and Provan , ].…”
Section: Discussionmentioning
confidence: 99%